2017
DOI: 10.1086/691261
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Networks and Neighborhood Social Organization

Abstract: Drawing on the social disorganization tradition and the social ecological perspective of Jane Jacobs, the authors hypothesize that neighborhoods composed of residents who intersect in space more frequently as a result of routine activities will exhibit higher levels of collective efficacy, intergenerational closure, and social network interaction and exchange. They develop this approach employing the concept of ecological networks—two-mode networks that indirectly link residents through spatial overlap in rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 64 publications
1
86
0
3
Order By: Relevance
“…The higher-order web of connections to other communities throughout the city is thus dependent on the economic resources and density of organizational life within a given community. Research based on the Los Angeles Family and Neighborhood Survey found that citywide ecological networks based on routine travel patterns across the city were also relevant to neighborhood social organization; in this case, the more residents were connected through shared visits to other neighborhoods in the city, the larger the increase in collective efficacy in home neighborhoods (32). Such chain-like movements of people and organizational ties define a core feature of urban higher-order social organization, solidifying neighborhood advantages and disadvantages.…”
Section: Social Mechanisms and Processes Underlying Sustainabilitymentioning
confidence: 99%
“…The higher-order web of connections to other communities throughout the city is thus dependent on the economic resources and density of organizational life within a given community. Research based on the Los Angeles Family and Neighborhood Survey found that citywide ecological networks based on routine travel patterns across the city were also relevant to neighborhood social organization; in this case, the more residents were connected through shared visits to other neighborhoods in the city, the larger the increase in collective efficacy in home neighborhoods (32). Such chain-like movements of people and organizational ties define a core feature of urban higher-order social organization, solidifying neighborhood advantages and disadvantages.…”
Section: Social Mechanisms and Processes Underlying Sustainabilitymentioning
confidence: 99%
“…The results of extant research on the consequences of variation in eco‐network structure point to the benefits of higher levels of eco‐network intensity for both key features of neighborhood social organization and youth behavior. Using data from Los Angeles, Browning and colleagues () found evidence of a beneficial effect of eco‐network intensity on changes in measures of collective efficacy, intergenerational closure, and reciprocated exchange among neighbors across two waves. Browning, Soller, and Jackson () found evidence of a protective effect of eco‐network intensity on the occurrence of individual‐level delinquency and substance use.…”
Section: Ecological Approaches To Neighborhood Crimementioning
confidence: 99%
“…As a result, estimating network structural characteristics based on a sample of households may result in biased estimates of eco-network intensity. Although Browning et al (2017) found that measures of the intensity of household intersection in an eco-network constructed from samples of tract-level populations were not subject to substantial bias, their simulations assumed a threshold level of within-tract sampling that is not often achieved in standard travel surveys. Consequently, we chose to employ population-level simulated data to facilitate unbiased representation of eco-network structures at the tract level.…”
Section: Microsimulation Data On Routine Activity Destinationsmentioning
confidence: 99%
“…In combination, these results address the conditions under which, for instance, mixed income housing and gentrifying neighborhoods will yield shared public space. To the extent that such public space sharing reinforces and enhances neighborhood social climates (Browning et al 2015), these findings may shed light on extant research linking inequality with other negative outcomes such as crime (Hipp 2007) and poor health (Wilkinson and Pickett 2009). …”
Section: Resultsmentioning
confidence: 89%